A stylistic Analysis of G. M. Hopkins’ Sea and the Skylark - Quadri, Kahkasha Moin; Ahmed, Haseeb; Shaikh, Suhel (International Journal of Language and Literary Studies, 2022)
This research examines the most-read poem, “The Sea and the Skylark," by G.M. Hopkins. Gerard Manley Hopkins was a great sonneteer, a patriot, an artist, a devotional poet of dogmatic Christianity, and a modern poet. "The Sea and the Skylark” was written by Hopkins in May 1877 in the town of Rhyl, close to St. Bueno’s College, where Hopkins stayed for three years to finish his theological studies. The poet composed this predictive sonnet when he was captivated by the corruption of mankind compared with the inherent innocence of nature. This paper examines numerous literary devices, namely, metaphor, imagery, symbolism, consonance, rhyme, rhythm, and Cynghanedd, which are the backbone of this poem. Artistic excellence and the chiastic effect also support this religious sonnet.